Efficient Light Trapping in Organic Solar Cell Using a Short-Pitched Hexagonal Array of Metallic Nanocylinders - Wenyan Wang; Ye Zhang; Ming Chen; Yuying Hao; Ting Ji; Furong Zhu; Yanxia Cui (IEEE Photonics Journal)
Plasmonic nanostructures have a great potential for enhancing light absorption of organic solar cells (OSCs). Our previous work has demonstrated that light absorption for OSCs with thin active layer can be significantly increased with a 1-D short-pitched metal grating, but the absorption enhancement is sensitive to the polarization of light and vanishes when the active layer is thicker than 60 nm. In this work, we extend the grating into 2-D space, specifically, with metallic nanocylinders packed in a hexagonal array embossed at the silver cathode. Numerical calculations indicate that the proposed OSC not only possesses polarization insensitivity but outperforms the corresponding equivalent planar device as well when the thickness of the active layer changes over a wide range from 40 to 120 nm. The absorption enhancement factor increases with the decrease of the active layer thickness, reaching 81.5% when the active layer is 40-nm thick. The evident enhancement in absorption is mainly due to the excitation of the strong dipole-like surface plasmon resonance, as well as their mutual coupling between neighboring nanocylinders. The present work could provide a promising route for the development of high-efficiency OSCs.